Elastic Behavior of Borate Glasses Containing Lead and Bismuth Oxides - Mehrdad Khanisanij; Haji Abdul Aziz Sidek (Advances in Materials Science and Engineering)
PbO and Bi2O3 binary borate glasses with different compositions, (MO)X(B2O3)1−X (M = Pb, Bi), have been characterized and ultrasonic velocity as well as density is taken into account. In addition, the results have been compared with those of Ag, K, and Li oxide borate glasses from others. The ultrasonic velocities (both longitudinal and transverse) and density for (PbO)X(B2O3)1−X and (Bi2O3)X(B2O3)1−X have been measured accurately and elastic moduli as well as hardness and Poisson’s ratio was determined. It has been demonstrated that density and ultrasonic velocities are enhanced by increasing PbO and Bi2O3 molar fraction with different values for each borate glass composition. However, the enhancement of ultrasonic velocities did not carry on continuously and after reaching a maximum point, they fell down dramatically. Both PbO and Bi2O3 showed almost similar glass improvement in case of density, ultrasonic velocity, and elastic moduli.